2016
DOI: 10.1177/1933719116638191
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Injury May Increase the Pregnancy Rate in Patients Undergoing Intrauterine Insemination: An Interventional Randomized Clinical Trial

Abstract: Endometrial injury using a Pipelle catheter in the stimulation cycle may improve pregnancy rates in women undergoing intrauterine insemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The majority of previous studies have indicated that local endometrial injury in the preceding cycle (proliferative phase and/or luteal phase) has positive effects on pregnancy outcomes in IVF/ICSI cycles . Similar to the present study, ESI was performed in the ovarian stimulation phase at the same cycle in other studies, and all reported beneficial effects of ESI on clinical outcomes in either the IUI or IVF cycles . Huang et al reported that a site‐specific hysteroscopic biopsy‐induced injury, generated on the posterior endometrium at the midline 10–15 mm from the fundus during days 4–7 of the ongoing COH cycle in six patients with repeated IVF failure, led to a pregnancy rate of 100% …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The majority of previous studies have indicated that local endometrial injury in the preceding cycle (proliferative phase and/or luteal phase) has positive effects on pregnancy outcomes in IVF/ICSI cycles . Similar to the present study, ESI was performed in the ovarian stimulation phase at the same cycle in other studies, and all reported beneficial effects of ESI on clinical outcomes in either the IUI or IVF cycles . Huang et al reported that a site‐specific hysteroscopic biopsy‐induced injury, generated on the posterior endometrium at the midline 10–15 mm from the fundus during days 4–7 of the ongoing COH cycle in six patients with repeated IVF failure, led to a pregnancy rate of 100% …”
Section: Discussionsupporting
confidence: 77%
“…Elsewhere, Wadhwa et al evaluated the impact of endometrial biopsy (EB) on IUI outcome, and concluded that EB conducted in the early follicular phase in the same cycle of stimulation is associated with better clinical pregnancy rate in comparison with EB performed in the luteal phase of the previous menstrual cycle . Consistent with the results of previous studies, Bahaa Eldin et al reported that ESI performed using pipelle catheter in the follicular phase (cycle day 5, 6 or 7) in the same stimulation cycle with IUI may improve the clinical pregnancy rate . This was inconsistent with the present study, although the present results are in agreement with Zarei et al , who found that ESI in the cycle before the IUI cycles did not improve the clinical pregnancy rate .…”
Section: Discussionmentioning
confidence: 62%
“…After the evaluation of the full publication text, five RCTs were additionally excluded: one study comparing the effects of office hysteroscopy with endometrial scratch versus office hysteroscopy on IUI outcomes (13), two clinical trials that were ongoing at the time of data collection (20,21), and two additional studies deemed ineligible for only investigating the effect of ESI on natural conception (22,23). In the end, a total of eight studies (2,8,15,16,(24)(25)(26)(27) were included in the present metaanalysis after applying our inclusion criteria (see Supplemental Fig. 1, available online).…”
Section: Study Selectionmentioning
confidence: 99%
“…From October 2015 to date, several new randomized controlled trials (RCTs) have evaluated ESI before IUI (2,8,15,16). Because the cumulative number of patients and studies almost doubled over this span of time, a new summary of evidence is needed.…”
mentioning
confidence: 99%
“…Wadhwa et al ., 2015, performed intervention before day 6 in same COS with IUI cycle and Bahaa Eldin et al . [ 28 ] performed endometrial injury on day 5, 6, or 7 of COS with IUI cycle. Thus, only a few studies have evaluated the role of endometrial scratching, done in early follicular phase of the same non-ART cycle [ Table 5 ].…”
Section: Discussionmentioning
confidence: 99%